Serum and urinary D-lactate in pediatric intestinal failure: clinical associations and reference values - Rita Halašová; Rana Ibrahim; Stanislava Balogová; Radek Štichhauer; Alena Tichá; Radomír Hyšpler; Vladana Skutilová; Filip Fencl; Kateřina Bajerová; Eva Karásková; Mária Véghová-Velgáňová; Peter Szitányi; et al. (Pediatric Research, 2026)
Abstract Background D-lactate, produced by intestinal microbiota or derived from the methylglyoxal pathway and diet, is converted by D-lactate dehydrogenase (LDHD) to pyruvate, with several known pathogenic variants of the gene. This study compared serum and urinary D-lactate concentrations across five patient groups and established reference values in healthy children. Methods In this cross-sectional study, 341 serum and urine samples from 129 pediatric patients were analyzed. The cohort comprised patients receiving home parenteral nutrition (PN, n = 19), after bowel adaptation (ADAPT, n = 28), with gastrostomy feeding (PEG, n = 13), other gastrointestinal disorders (GI, n = 14), and healthy controls (HC, n = 55). D-lactate was measured via enzymatic spectrophotometric assay. A genetic sub-analysis assessed pathogenic LDHD variants. Results Median serum and urinary D-lactate concentrations in healthy controls were 28.5 μmol/L (IQR 25–34.25) and 400 μmol/L (IQR 193–722), respectively. Both serum ( p < 0.001) and urine ( p = 0.011) D-lactate concentrations were higher in the ADAPT group compared to healthy controls. No pathogenic LDHD variants were identified. Conclusion Children after bowel adaptation have higher serum and urine D-lactate concentrations compared to healthy controls. Reference values for serum and urinary D-lactate were defined. Impact This is the first study to provide reference values for serum and urinary D-lactate concentrations in healthy children (serum: 28.5 µmol/L (IQR: 25–34.25 µmol/L); urine: 400 µmol/L (IQR: 193–722 µmol/L)). Children after bowel adaptation exhibited higher D-lactate concentrations in both serum and urine compared to healthy controls. Higher serum and urinary D-lactate levels were associated with the presence of an intestinal anastomosis.